(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This study aimed to reveal the influence of Canon Pachelbel’s music on student motivation in reading performances. The focus of this research was the influence of Canon Pachelbel’s music on student motivation in reading performances. This type of research was descriptive and qualitative. Revealing the Effect of Canon Pachelbel’s Music on Students’ Motivation in Reading Performances. The data collection method was carried out by distributing questionnaires to the MA Mizanul Ulum Sanrobone Takalar. The data consisted of two categories, namely primary data which was the main data obtained from core informants, and secondary data in the form of data from several refeanswers that were relevant to the research object of this research. The data was then analyzed using the theory of Miles and Huberman, namely data reduction, data presentation, as well as concluding, and verification. The results of this study indicate that the Effect of Canon Pachelbel’s Music on Students’ Motivation in Reading Performances Analysis of scores on a questionnaire containing the influence of Canon Pachelbel’s classical music can improve students’ reading achievement. From the positive questionnaire. Based on students’ answers to positive statements 76% were in the very high category, while 53% were negative statements in the low category. The gap between the positive and negative categories showed that Pachelbel’s Canon music was improved the reading ability of MA Mizanul Ulum Sanrobone Takalar students in the high category so it said that Pachelbel’s Canon music affects increasing reading achievement in MA Mizanul Ulum Sanrobone Takalar students. So that students was improved reading skills using Pachelbel’s canon classical music method.